Hành vi tự chăm sóc sức khỏe tâm thần của công nhân: Tổng quan nghiên cứu và định hướng tiếp cận trong bối cảnh Việt Nam - Võ Minh, Thành; Đinh Phương Duy, Đinh Phương Duy; Võ Thị Tường Vy , Võ Thị Tường Vy (Tạp chí Giáo dục, 2026)
Workers’ mental health has become an increasingly important concern as adverse working conditions and psychosocial risks continue to grow. However, research on mental health self-care behaviour among workers in Vietnam remains limited. This study presents a narrative review of the literature to clarify the conceptualization of workers’ mental health self-care behaviour, identify its influencing factors, and examine research gaps in the Vietnamese context. Literature was retrieved from Google Scholar, PubMed, ScienceDirect, SpringerLink, Taylor & Francis Online, and World Health Organization and International Labour Organization sources. Priority was given to publications from 2014 to 2026, while selected seminal studies published before 2014 were included to establish the theoretical foundation. The review identified four main findings. First, workers, particularly migrant workers and those with limited support resources, are at high risk of mental health problems and face barriers to accessing formal mental health services. Second, mental health self-care behaviour should be understood as a psychological and behavioural process involving mental health awareness, emotional regulation, stress management, recovery from work, maintenance of social support, and help-seeking when needed. Third, this behaviour is shaped by both individual resources and organizational and workplace factors. Fourth, research in Vietnam has paid limited attention to the conceptual structure, measurement, influencing factors, and interventions related to workers’ mental health self-care behaviour. The findings suggest that future research and interventions should integrate the strengthening of workers’ self-care capacity with organizational strategies to reduce psychosocial risks and improve access to mental health support.